Etnoecologia e conservação em áreas naturais protegidas: incorporando o saber local na manutenção do Parque Nacional do Superagui - Pedroso Júnior, Nelson Novaes (Universidade Federal de São Carlos, 2002)
Surely, the human s economic legacy has been identified as a main factor to the exploitation of nature. However, and very often, we can realize from the human s history, that popular imaginary has contributed to the environmental transformation. The establishment of particular costumes, in different historical periods, can tell us about intrinsic relationship between culture and nature. In this context, the Environmental Protected Area (EPA) of Guaraqueçaba, to the North littoral of Paraná State, where the National Park of Superagüi (Parque Nacional do Superagui) is located, represents one of the major and well preserved continuous remainder of the Brazilian Atlantic Rainforest, sheltering more than 50 human communities that live basically from the fishery practice and subsistence agriculture. However, in the last decades this region has passed by an intensification on the transformation of the economical, social and cultural processes, especially due to the increasing tourism, and real state agency speculation, and from the protected natural areas creation, and also the strong reduction of the agriculture for the specialization and intensification of fishery activities, led by the introduction of motorized boats. As a consequence, the local knowledge, based upon experiences and maintained through oral history, is getting lost. Nevertheless, besides scientific knowledge, it may represent an essential tool for the management and conservation of a region. In this manner, this study aims to conserve both diversities, popular and scientific. Thorough analysis of local knowledge related to terrestrial fauna of the National Park of Superagüi, this research sets sighs scientific examination of soil occupation changes and assessment complexity, giving ethnoecological elements and methodology to weave a net of activities of Environmental Education.
Keywords: Ecologia humana; Biologia da conservação; Caiçaras; Educação ambiental; Etnoecologia; Fauna terrestre; Unidades de conservação; Ethnoecology; Terrestrial fauna; Protected natural areas; Caiçaras; Environmental education; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS